2011
DOI: 10.1007/s00296-010-1733-6
|View full text |Cite
|
Sign up to set email alerts
|

The expression of RANKL and OPG in the various grades of osteoarthritic cartilage

Abstract: The objective of the study was to determine whether cartilage expression of the bone regulating molecules receptor activator of nuclear factor κB ligand (RANKL) and osteoprotegerin (OPG) varies between the different grades of osteoarthritis (OA). Cartilage samples were obtained from 30 patients undergoing total hip/knee replacement surgery. Tissue sections were stained with Safranin O and graded. Immunohistochemical staining was then performed, and levels of RANKL and OPG expression were assessed using a semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 25 publications
(34 reference statements)
2
33
1
6
Order By: Relevance
“…Changes in subchondral bone turnover precede changes in cartilage (see references in Kwan Tat et al 9) and pain-related molecules have been detected in OA subchondral bone 10. Dynamic changes in bone turnover result from increased activity of osteoclasts and osteoblasts, and the osteoprotegerin (OPG)/receptor activator of NF-κB (RANK)/receptor activator of NF-κB ligand (RANKL) system is critical for this activity 9 11 12. Osteoclast activation is associated with reduced extracellular pH, and release of proteases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in subchondral bone turnover precede changes in cartilage (see references in Kwan Tat et al 9) and pain-related molecules have been detected in OA subchondral bone 10. Dynamic changes in bone turnover result from increased activity of osteoclasts and osteoblasts, and the osteoprotegerin (OPG)/receptor activator of NF-κB (RANK)/receptor activator of NF-κB ligand (RANKL) system is critical for this activity 9 11 12. Osteoclast activation is associated with reduced extracellular pH, and release of proteases.…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance in the OPG/RANKL system, both in synovial fluid and serum, has been associated with OA severity in man 12 23. Exogenous treatment with a modified OPG (OPG-Fc) attenuates bone loss in a rodent model of inflammatory arthritis24 and, although effects on arthritis pain were not reported, OPG inhibited bone cancer-induced pain behaviour 25.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-13 is predominantly localized in the deeper layers of cartilage (29). In a study performed by Upton et al (30), increased RANKL mRNA expression levels were observed in grade II OA cartilage, particularly in the deep layer of cartilage. Various previous studies have reported that RANKL is expressed by chondrocytes in normal and OA cartilage (12,31).…”
Section: Discussionmentioning
confidence: 94%
“…A previous biochemical analysis of the circulating levels of macromolecules released from cartilage and bone in humans revealed a convergence of the pathological processes in cartilage and subchondral bone in OA at each stage (6). Furthermore, a previous study demonstrated that RANKL secreted by chondrocytes diffuse across the thin layer of calcified cartilage into subchondral bone, resulting in morphological changes to subchondral bone, which is an important factor in OA pathophysiology (30). Combined with the results of the present study, we hypothesize that RANKL overexpression in subchondral bone may diffuse into cartilage and elevate MMP-13 expression levels, which subsequently accelerates cartilage degradation.…”
Section: Discussionmentioning
confidence: 98%
“…Большинство авторов признают, что ключевую роль в регуляции метаболизма костных клеток играет молекуляр-ная триада: остеопротегерин / рецептор, активирующий фактор транскрипции NFκB / лиганд этого рецептора (ОPG/RANK/RANKL) [22]. Одним из факторов, регулиру-ющих функционирование данной триады, является уро-вень половых гормонов.…”
Section: таблицаunclassified